An Ideal Model for Combating Child Sexual Violence - Rasdi Rasdi; Winarsih Winarsih; Didik Purnomo; Sonny Saptoajie Wicaksono; Ridwan Arifin (Universitas Negeri Semarang, 2026)
Child sexual violence remains a serious challenge in Indonesia despite the existence of various legal instruments, including the 1945 Constitution, the Child Protection Law, and Law Number 12 of 2022 concerning Sexual Violence Crimes. The increasing number of cases indicates that existing legal measures have not been fully effective in preventing and addressing child sexual violence. Previous studies have primarily focused on punishment mechanisms and specific sanctions, while limited attention has been given to the integration of penal and non-penal approaches within a comprehensive criminal policy framework. This study aims to analyze the factors contributing to child sexual violence and formulate an integrated criminal policy model to address this issue. The research employed normative juridical legal research using statutory and conceptual approaches. The analysis was conducted through a qualitative doctrinal examination of primary and secondary legal materials. The findings revealed that child sexual violence is influenced by multiple factors, including the psychological, moral, and behavioral characteristics of offenders, as well as social, cultural, economic, educational, and technological factors that create conditions conducive to such crimes. The study argues that reliance on penal measures alone is insufficient to provide effective protection for children. An integrated criminal policy combining penal and non-penal approaches is therefore required. This model incorporates law enforcement, child protection mechanisms, family and community participation, educational interventions, and offender rehabilitation. The proposed framework contributes to criminal law policy discourse by offering a more comprehensive strategy for preventing child sexual violence while promoting victim protection, offender rehabilitation, and social reintegration.